2013
DOI: 10.12688/f1000research.2-167.v1
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the promptness and quality of care of road traffic incident victims in Peru: a cross-sectional, active surveillance study

Abstract: Background: Road injuries are the second-leading cause of disease and injury in the Andean region of South America. Adequate management of road traffic crash victims is important to prevent and reduce deaths and serious long-term injuries. Objective: To evaluate the promptness of health care services provided to those injured in road traffic incidents (RTIs) and the satisfaction with those services during the pre-hospital and hospital periods. Methods: We conducted a cross-sectional study with active surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
1
1
Order By: Relevance
“…In Tarrahi et al survey in health centers of Khoram Abad city in Iran, in expectations part, assurance and responsiveness had the maximum and minimum mean scores that were in line with the results of the present study. In the current investigation, regarding the patients' perceptions, reliability and responsiveness had the highest and lowest mean, respectively (31). In another study conducted by Bahadori et al in army hospitals, assurance and tangible dimensions were found to have the maximum and minimum mean score, which was not in line with the findings of the present study (32).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In Tarrahi et al survey in health centers of Khoram Abad city in Iran, in expectations part, assurance and responsiveness had the maximum and minimum mean scores that were in line with the results of the present study. In the current investigation, regarding the patients' perceptions, reliability and responsiveness had the highest and lowest mean, respectively (31). In another study conducted by Bahadori et al in army hospitals, assurance and tangible dimensions were found to have the maximum and minimum mean score, which was not in line with the findings of the present study (32).…”
Section: Discussioncontrasting
confidence: 96%
“…In another study conducted by Bahadori et al in army hospitals, assurance and tangible dimensions were found to have the maximum and minimum mean score, which was not in line with the findings of the present study (32). On the other hand, in a survey performed in Peru by Miranda et al (31) on people who suffered from traffic accident, assurance dimension was revealed to have the lowest mean. Moreover, despite the poor correlation in responsiveness dimension, the results showed correlations between five dimensions of service quality in the perceptions and expectations parts.…”
Section: Discussionmentioning
confidence: 88%
“…Researches affirm that the transportation of the patient to the appropriate service directly influences his/her satisfaction with the service, thus providing continuity of care and its resolution 24, 25 . The transport of the patient to a hospital that presents problems of overcrowding may have influenced the negative evaluation of this indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Mustafa et al showed that, in hospitals in Egypt, patients’ expectations concerning the quality of the healthcare services were affected on their stratification from types of services and hospitals (public or private) (18). A study by Miranda and et al on 644 patients injured by vehicle accidents in Peru in 2013 indicated that 95% of patients in public hospitals and 78% of patients in private hospitals were dissatisfied with the quality of the healthcare services provided by these hospitals (19). Tabibi et al showed that there are significant differences between patients’ expectations and their perception of the actual quality of healthcare.…”
Section: Introductionmentioning
confidence: 99%